Assessment of Self-care Practices among Heart Failure Patients in District Head Quarter Hospital Timergara Dir Lower: Self-care Practices among Heart Failure Patients - Sohail Mohammad; Naz, Najma; Nasir Khan, Muhammad; Rahim Khan, Muhammad; Haq, Sami Ul (Pakistan Journal of Health Sciences, 2023)
In both hospitals and the community, nurses play a critical part in the provision of healthcare. The improvement of heart failure patients’ self-care behaviors is greatly helped by nurses. Objective: To determine the level of self-care practices among heart failure patients at the District Headquarter Hospital of Timergara Dir Lower. Methods: A cross sectional study design was used to determine the level of self-care practices among heart failure patients. Self-Care Heart Failure Index (SCHFI) version 7.2 was used for data collection. After receiving written informed consent, 150 hospitalized heart failure patients were recruited through a consecutive sampling technique from the Department of Internal Medicine and Cardiology at DHQ Hospital Timergara Dir Lower. Data were analyzed with SPSS version 26.0. Results: It was found out that 44% of the study participants were females, 56% were males, 80% were married, 6% were illiterate and 86% had caregivers at home. Moreover, the mean score of the self-care subscales were inadequate (i.e., self-care maintenance: 68.5, symptoms perception: 67.26, self-care management: 68.56 and self-care confidence: 69.15, cutoff value: 70). The level of self-care was significantly associated with gender. In-addition, the marital status was significantly associated with the level of self-care in the sub-domains of self-care maintenance (p=0.011) and self-care management (p=0.001). Conclusions: Results of the study specified that majority of the heart failure patients had lack of adequate self-care practices. Therefore, efforts should be done to help them in performing an adequate self-care activity to remain healthy and reduce their hospital re-admissions.